A Thematic Analysis of Nurses’ Experiences with Open Visiting Hours on Medical Units - Raghubir, Angelina (Université d'Ottawa / University of Ottawa, 2019)
Aim: To describe medical nurses’ experiences caring for patients and families within an environment with open visiting hours (OVH). Background: OVH is an approach where families and friends can visit patients without restrictions. OVH is a strategy used by hospitals to promote patient-and-family-centered care (PFCC). In an OVH environment, the increased presence of family can alter nurses’ working environments. However, research examining nurses’ perspectives on OVH is limited. As OVH becomes more widely implemented, it is essential to understand the influence of OVH on the nurse. Design: A qualitative descriptive approach was used. Methods: Semi-structured interviews were conducted with 10 registered nurses on two medical units in a large urban Canadian hospital. Thematic analysis was used to analyze the data inductively. Strategies were used to enhance rigour. Results: Four main themes resulted which described participants’ experiences with OVH as they related to the processes and philosophy of OVH, the care of patients and family, and the influence families had on patient care and nurses working environments. An overarching theme of Reliance and Resistance reflected participants’ mixed feelings toward OVH. While OVH facilitated PFCC and alleviated nurses’ work, at times it also hindered opportunities for nurses to get to know patients and added to their work. Further, increased family presence created challenges related to space, overcrowding, increased noise levels, and created concerns about safety. Conclusion: The findings add to an understanding of the clinical realities of OVH from the perspectives of medical nurses, and the potential implications for PFCC and nurses’ working environment. Relevance to clinical practice: OVH creates an environment to foster PFCC. However, nurses may benefit from training to facilitate communication and engagement with families. Organizations who wish to implement OVH should consider how contextual factors may influence nurses’ environments and their practice.
Keywords: Open visiting hours; 24-hour visiting